Implementasi Terapi Relaksasi Benson Untuk Menurunkan Intensitas Nyeri Pasien Post Operasi Turp pada Penderita Benigna Prostat Hyperplasia di Ruangan Anggrek Rumah Sakit Vita Insani Pematangsiantar - Alwi, Muhammad Rizad; Wani Damanik, Derma (Journal of Comprehensive Science, 2024)
Transurethal Urethral Resection of the Prostate (TURP) is a surgical procedure to treat Benign Prostate Hyperplasia (BPH) by removing tissue from the side of the prostate zone. Surgery will cause pain and one way to relieve pain is the Benson relaxation technique. Benson relaxation is a relaxation technique that combines deep breathing relaxation and beliefs that can relax and reduce pain. This research design uses the Case Study method. The sampling method used is purposive sampling. The samples taken were 2 respondents, namely post-operative TURP patients with BPH who were hospitalized at Vita Insani Hospital, Pematangsiantar. The results showed that the pain experienced by post TURP surgery patients in BPH sufferers decreased as seen on the pain scale. Mr. H, moderate pain scale (6) to mild pain (2) and Mr. P, moderate pain scale (5) to mild pain (1) Benson relaxation therapy was effective in post-TURP surgery cases in reducing pain intensity. Nurses are expected to be able to accompany patients to apply Benson relaxation therapy in an effort to reduce pain in post-TURP surgery patients.